MYCOBIOTA OF TERMITES OF THE GENUS ANACANTHOTERMES - Sapayeva Munisa Norbekovna; Doschanova Manzura Babajonovna; Ruzmetov Rasul Sobirovich (Zeta Repository, 2023)
Various biological, chemical and physical processes take place in the soil. Soil is a natural habitat for various physiological groups of microorganisms and many soil insects. The structure and composition of termite nest soil differs from the surrounding soil. It contains clay from the deep layers of soil that the termite family uses for building purposes and a large amount of other organic matter. Nests of the Turkestan termite are completely hidden on the soil surface, and the nests of the Greater Caspian termite, on the contrary, are clearly visible on the soil surface and represent a mound (roundness) of mud with a height of 20-50 cm [113; pp. 22-24]. Termite habitats are home to many fungi, some of which compete with termite food. Such competition can lead to separation of habitats, and subsequently to interactions such as symbiosis, parasitism, or pathogenicity. During the regular feeding, nesting and other activities of termites, various fungi infect their bodies. Mycobiota of termites plays an important role in their life activities. In all seasons of 2018-2020, in our studies related to the study of the mycobiota species composition of termites in the Khorezm oasis, we found fungi in termite nests and their internal chambers, on the walls of passageways, in the mouth, in the body, and in the digestive system. the presence of spores and hyphae was noted. The species composition of the fungi growing on the stems of sunflower (Helianthus annuus L.) was studied in relation to its use as a forage base against termites. In our research conducted under different conditions of the Khorezm oasis, 31 types of fungi were isolated from the termite body, soil near the termite nest, nest chambers and food, and the species composition was determined (Table 4.3.1).